Condensed Matter Theories, Volume 22 : Proceedings of the International Workshop. - Reinholz, Heidi (World Scientific Publishing Company, 2007)
This series on condensed matter theories provides a forum for advanced theoretical research in quantum many-body theory. The contributions are highly interdisciplinary, emphasizing common concerns among theorists who apply many-particle methods in such diverse areas as solid-state, low-temperature, statistical, nuclear, particle, and biological physics, as well as in quantum field theory, quantum information and the theory of complex systems. Each individual contribution is preceded by an extended introduction to the topic treated. Useful details not normally presented in journal articles can.